Development of SAMR-Based Instructional Tools to Improve Teacher Candidate Productivity - Ida Rindaningsih; Eni Fariyatul Fahyuni; Najih Anwar (Jurnal Inovasi Pendidikan dan Sains, 2025)
This study aims to develop and validate a SAMR based instructional toolkit designed to enhance teacher candidates’ productivity through reflective digital pedagogy. Employing the Research and Development (R&D) method using the Borg & Gall and ADDIE models, the research involved five systematic stages: needs analysis, design and development, expert validation, field testing, and evaluation. The needs analysis with 45 pre-service teachers revealed that 82% faced difficulties integrating digital tools effectively, while 76% experienced time inefficiency in lesson planning. The prototype, developed through iterative co-design, achieved a content validity score of 0.93 (S-CVI/Ave), indicating excellent feasibility. Field testing with 60 participants (experimental and control groups) showed a significant improvement in productivity (t(58) = 5.87, p < 0.001; g = 0.65), while average lesson-planning time decreased by 39%. Qualitative reflections confirmed that the toolkit’s structured digital scaffolding fostered higher reflective awareness and creative instructional design. The final product proved valid, practical, and effective in improving pedagogical innovation among teacher candidates. These findings extend the SAMR framework into an empirical R&D context and contribute to the implementation of Merdeka Belajar Kampus Merdeka (MBKM) policies through digitally empowered reflective teaching